Assessment of the control measures of the category A diseases of Animal Health Law: sheep and goat pox. (27th December 2021) - ,; Nielsen, Søren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, José Luis; Gortázar, Christian; Herskin, Mette; Michel, Virginie; et al.
Abstract: EFSA received a mandate from the European Commission to assess the effectiveness of some of the control measures against diseases included in the Category A list according to Regulation (EU) 2016/429 on transmissible animal diseases ('Animal Health Law'). This opinion belongs to a series of opinions where these control measures will be assessed, with this opinion covering the assessment of control measures for sheep and goat pox. In this opinion, EFSA and the AHAW Panel of experts review the effectiveness of: (i) clinical and laboratory sampling procedures, (ii) monitoring period and (iii) the minimum radii of the protection and surveillance zones, and the minimum length of time the measures should be applied in these zones. The general methodology used for this series of opinions has been published elsewhere; nonetheless, the transmission kernels used for the assessment of the minimum radii of the protection and surveillance zones are shown. Several scenarios for which these control measures had to be assessed were designed and agreed prior to the start of the assessment. Different risk‐based sampling procedures based on clinical visits and laboratory testing are assessed in case of outbreak suspicion, granting animal movements and for repopulation purposes. The monitoring period of 21 days was assessed as effective. The estimated probability of transmission beyond the protection zone of 3 km radius from an infectious establishment is 9.6% (95% CI: 3.1–25.8%) and 2.3% (95% CI: 1–5.5%) for the surveillance zone of 10 km radius. This may be considered sufficient to contain the disease spread (95% probability of containing transmission corresponds to 5.3 Km). To contain 99% of the spread, the radius should be increased to 19.4 km (95% CI: 9.8–26.8). This may increase the number of farms in the surveillance zone, since the area would increase fourfold.